Effects of Latino children on their mothers' dietary intake and dietary behaviors: The role of children's acculturation and the mother-child acculturation gap. (October 2017) - Soto, Sandra H.; Arredondo, Elva M.; Marcus, Bess; Shakya, Holly B.; Roesch, Scott; Ayala, Guadalupe X.
Abstract: Rationale: Research shows that acculturation is important to Latinas' dietary intake and related behaviors. Although evidence suggests children may also play a role, it remains unclear whether children's acculturation is related to mothers' dietary intake/behaviors. Objectives: We examined the relationship between Latino children's acculturation and mothers' dietary intake/behaviors. We also examined the mother-child acculturation gap to identify dyad characteristics associated with mothers' diet. Methods: Baseline surveys were collected in 2010 from 314 Latino mother-child (7–13 years old) dyads of Mexican-origin enrolled in a family-based dietary intervention in Southern California, USA. Mother's daily intake of fruits, vegetables, and sugary beverages, percent of calories from fat, weekly away-from-home eating, and percent of weekly grocery dollars spent on fruits and vegetables were assessed via self-report. Mothers' and children's bidimensional acculturation were examined using acculturation groups (e.g., assimilated, bicultural) derived from Hispanic and non-Hispanic dimensions of language. We also assessed the acculturation gap between mothers and children with the a) difference in acculturation between mothers' and children's continuous acculturation scores and b) mother-child acculturation gap typologies (e.g., traditional mothers of assimilated children). Results: Findings show that having an assimilated versus a bicultural child was negatively associated with mothers' vegetable intake and positively associated with mothers' sugary beverage intake, percent of calories from fat, and frequency of away-from-home eating, regardless of mothers' acculturation. Traditional mothers of assimilated children reported more sugary beverage intake, calories from fat, and more frequent away-from-home eating than traditional mothers of bicultural children. Conclusion: Results suggest that children's acculturation is associated with their mothers' dietary intake/behaviors and traditional mothers of assimilated children require more attention in future research. Highlights: We modeled associations between children's acculturation and Latina mothers' diet. Mothers of assimilated versus bicultural children had a low diet quality. Culturally traditional mothers of assimilated children had the lowest quality diet. Future work should consider the role of children and culture on adult Latinas' diet.